The Representation of Women in Li Young-Lee’s Poems - Asthereni, Patricia Vania Septhine Yulia (OKARA: Jurnal Bahasa dan Sastra, 2020)
Patriarchy has become the central attention of feminism because its practices expand to many different fields in society, such as politics, law, power relations between male and female and literary works, such as poems. Lee, as a poet with a lot of notable achievements, also internalises his patriarchal ideology through the women representation portrayed in "Persimmons", "Braiding", "Pillow", "Early in the Morning" and "This Room and Everything in It". This study analyses five of Lee's poems utilising close reading to discover the exercises of patriarchy to the female characters in Lee's poems. The points are proven by six structures of patriarchal system, which cover six aspects of social life namely mode of production; salaried employment; state; male violence; culture, and relationship in sexuality. Women's portrayal in Lee's poems specifically reveals patriarchal relations in sexuality. This study concludes that Lee's portrayal of women in his poems is indeed patriarchal by means of (1) characterising women as weak and passive; (2) male dominating as evident in sexual relationship and (3) making women as sex objects.